PENENTUAN STRATEGI PEMASARAN DALAM MEMPERTAHANKAN EKSISTENSI DAN MENGADAPI PERSAINGAN (Studi Kasus Pada Gemilang Art Glass Di Modo) - Zulkifli Lubis; Kemal Farouq Mauladi; Mohammad Rizal Nur Irawan (STIE Mahardhika, 2020)
Appropriate marketing strategies are needed to increase sales and achieve the goals of a company. This research was conducted to determine marketing strategies using SWOT analysis so that a company is able to maintain its existence and face competition and what is the most appropriate strategy that can be applied to a company. The research was conducted at Gemilang Art Glass Company in Modo. From the results of the SWOT analysis showed that the strength (strength) 3.66, and weakness (weakness) 0.76, opportunity (opportunity) 2.86, and the threat (threatr) 1.28. From the SWOT diagram above can be seen from the difference in strength (strength) and weakness (weakness) score higher strength (strength) with a difference (+) 2.9, while the difference in the opportunity (opportunity) and threat (threat) score value is higher the opportunity (opportunity) with a difference (+) 1.58. So that it clearly shows that Gemilang Art Glass has been dealing with the right path by continuing to carry out aggressive strategies to increase sales. Based on the above results it can be concluded that an aggressive strategy that can be done is the S-O strategy. The strategy includes improving quality and service so that consumers feel satisfied and comfortable and attract new customers, increase company capacity by utilizing the ability of teamwork and company experience to reach potential markets, provide information about new products to consumers by using internet technology, and by treating employees well and establish a sense of brotherhood will make employees always professional and disciplined in carrying out the work.